PROBLEM RELATED PAPER TENSION AND ITS SOLUTION IN NEWSPAPER PRODUCTION USING WEB OFFSET PRINTING MACHINE - Mawan Nugraha; A Sarmada; Ari Dwi Yulianto (Politeknik Negeri Media Kreatif, 2020)
In-depth observations have been made on the web printing process for newspaper production. Observations were made to identify problems related to the tension of the roll paper used in the production of newspapers. The problem of roll-paper tension is observed from the main material, the upstream process (Reelstand Unit), the printing process and its supporting units such as the wetting unit, inking unit and in the folder unit which is a contineous process. From observing the problems in the printing process, the causes and solutions to the problems were identified which were then used as an operating standard reference for the newspaper production using a web offset printing machine.Keywords—web offset printing machine, newspaper, paper tension